2019
DOI: 10.1161/strokeaha.118.022923
|View full text |Cite
|
Sign up to set email alerts
|

Functional Magnetic Resonance Imaging of Inhibitory Control Reveals Decreased Blood Oxygen Level Dependent Effect in Cerebral Autosomal Dominant Arteriopathy With Subcortical Infarcts and Leukoencephalopathy

Abstract: Background and Purpose— Small-vessel damage in cerebral autosomal dominant arteriopathy with subcortical infarcts and leukoencephalopathy (CADASIL) is associated with impaired vascular constriction and dilation. We used a functional magnetic resonance imaging task with an event-related design of stimulus to explore the anticipated abnormally decreased blood oxygen level dependent effect in CADASIL. Methods— Twenty-one CADASIL patients and 16 healthy con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Our recent resting-state amplitude of low-frequency fluctuation (ALFF) analyses revealed negative associations between the ALFF values of the left cerebellar anterior and posterior lobes, and executive function scores [18]. An event-related Go/No-go task study on CADASIL patients revealed lower blood oxygen level-dependent (BOLD) effects in the alerting network and in areas involved in executive functions, possibly reflecting hemodynamic responses that developed secondary to small-vessel changes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Our recent resting-state amplitude of low-frequency fluctuation (ALFF) analyses revealed negative associations between the ALFF values of the left cerebellar anterior and posterior lobes, and executive function scores [18]. An event-related Go/No-go task study on CADASIL patients revealed lower blood oxygen level-dependent (BOLD) effects in the alerting network and in areas involved in executive functions, possibly reflecting hemodynamic responses that developed secondary to small-vessel changes [19].…”
Section: Introductionmentioning
confidence: 99%
“…Due to underlying SVD, it is difficult to ascertain to what extent decreased BOLD reflects decreased regional tissue blood flow or intrinsic functional changes of the cerebral cortex. 25 We did not evaluate our patients with neuropsychological tests exploring the inhibitory and attention functions. There is little doubt that an increase in rsfMRI acquisition time and the use of a higher number of diffusion weighting gradient directions as well as higher number of signal acquisitions would have further improved the quality of our data.…”
Section: Discussionmentioning
confidence: 99%
“…There is a broad, general limitation on the way in which BOLD fMRI results in CADASIL patients are interpreted. Due to underlying SVD, it is difficult to ascertain to what extent decreased BOLD reflects decreased regional tissue blood flow or intrinsic functional changes of the cerebral cortex 25 . We did not evaluate our patients with neuropsychological tests exploring the inhibitory and attention functions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations